Accounting for GDP– A study of epistemic strategies when calculating the quarterly economy - Du Rietz, Sabina (Accounting, Organizations and Society, 2024)
Previous studies of macroeconomic accounting have focused on the conceptual and political development of national accounts and how such theoretical concepts generate economic reality. By turning focus to the calculative practices of macroeconomic accounting, studying the Norwegian Quarterly National Accounts (QNA), the present work underlines that the national economy is not only constituted in the political discourse of growth and within international classifications, but also within the everyday processes of calculating the numbers. It shows how the QNA team struggles to adhere to the formal classifications and find reliable empirical accounts that matches them. In such situations, epistemic strategies are employed to handle the “gaps” and misalignments between the formal classifications and the everyday calculative practice. By theorizing the validation and support of weak numbers within a calculative culture shaped by the handling of second-order measurements and interrupted representations, the present study contributes to an emerging accounting literature on interrupted and hyperreal representations.